The Certifiable Salesperson - Hopkins, Tom (Recorded Books, Inc., 2008)
Tom Hopkins, the world's leading expert on salesmanship and author of 11 books, joins forces with award-winning speaker Laura Laaman to create a fool-proof guide to being a successful salesperson. This handbook focuses on selling techniques, from handshakes and clothing to networking and presentations.